Regional structural analysis of rock slope failure types, mechanisms and controlling bedrock structures in Kåfjorden, Troms - Andresen, Maren Lund (UiT Norges arktiske universitet, 2018)
Unstable areas producing rock slope failures come with large consequences. The understanding of why and where they might occur is necessary to mitigate damage and prevent casualties. A total of 133 unstable rock slopes have been detected in Troms, Northern Norway, evidencing that a great focus on these geohazards is important. This study has focused on seven unstable rock slopes in Kåfjorden, Troms, with the aim of analyzing the controlling bedrock structures of each unstable rock slope. Whether regional trends of lineaments are controlling of the unstable areas have also been of interest. The failure-enhancing structures are (i) Caledonian foliation, (ii) a combination of foliation and post-Caledonian brittle structures, and (iii) post-Caledonian brittle fractures. Five of the studied rock slopes are located on the northeastern side of the fjord and two are located on the southwestern side of the valley. The Caledonian bedrock comprises a well-developed SW –dipping foliation on the NE side of the fjord that alone controls three of the unstable rock slopes. The foliation dips NW –ward on the SW side of the fjord. Four localities are found controlled by a combination of foliation and the brittle fractures, while one sub-locality is interpreted to be controlled by the post-Caledonian brittle fractures. Six different failure mechanisms are interpreted for the localities, including sub-localities. Regarding the regional lineaments, two of the trends parallel to the brittle fractures of the localities are interpreted to be controlling, dominantly the NW-SE –trending, with the E-W –trending ones as subordinate. These orientations are parallel to the fjord of Kåfjorden.